2010
DOI: 10.1038/aps.2010.10
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3β regulates astrocytic differentiation of U87-MG human glioblastoma cells

Abstract: Aim: To evaluate the role of glycogen synthase kinase-3β (GSK-3β) in the induced differentiation of human glioblastoma cells. Methods: Cell proliferation was determined by bromodeoxyuridine (BrdU) incorporation assay. The protein level of p-GSK-3β, GSK-3β, glial fibrillary acidic protein (GFAP) and proliferating cell nuclear antigen (PCNA) were determined using Western blots. The overexpression of mutant GSK-3β was analyzed by immunocytochemistry. Results: The biotoxin cholera toxin is capable of inducing diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…the reduction of SCs in solid tumors by treatment with agents that induce differentiation [ 55 ], has been proposed as a novel therapeutic approach. In GBM PTEN has been putatively identified to contribute to differentiation [ 56 , 42 ], however, in contrast to some recent publications [ 41 , 42 , 57 , 58 ], several of which focus on established cell lines [ 57 , 58 ], we find no evidence of PI3K signaling contributing to the differentiation from SC to DC, except in a trivial sense. Alterations in the number of DCs (defined morphologically and by GFAP expression) that can be induced from SCs in the presence of absence of PI-103 are most likely due to the sharp decrease in proliferation upon PI3K inhibition and not a direct effect of an altered differentiation potential.…”
Section: Discussioncontrasting
confidence: 99%
“…the reduction of SCs in solid tumors by treatment with agents that induce differentiation [ 55 ], has been proposed as a novel therapeutic approach. In GBM PTEN has been putatively identified to contribute to differentiation [ 56 , 42 ], however, in contrast to some recent publications [ 41 , 42 , 57 , 58 ], several of which focus on established cell lines [ 57 , 58 ], we find no evidence of PI3K signaling contributing to the differentiation from SC to DC, except in a trivial sense. Alterations in the number of DCs (defined morphologically and by GFAP expression) that can be induced from SCs in the presence of absence of PI-103 are most likely due to the sharp decrease in proliferation upon PI3K inhibition and not a direct effect of an altered differentiation potential.…”
Section: Discussioncontrasting
confidence: 99%
“…The MTT results are in accordance with the enzyme assay results with IC50 37 μM and > 100 μM for compounds 102 and 4, respectively (Table 1). The results, confirm the importance of GSK-3β in cancer progression and open new avenues for the use of the synthon I derivatives GSK-3β inhibitors as anti-cancer drugs [18].…”
Section: Gsk-3β Inhibitors Activitysupporting
confidence: 70%
“…Next step was to determine if these compounds have any pharmacological activities as potential anticancer treatments. The U-87 glioma cell line was used in the MTT assay as it is known to express GSK-3β [18]. The most active (compound 102) and the least active (compound 4) compounds from the enzyme assay were chosen to assess their anti-proliferative activity.…”
Section: Gsk-3β Inhibitors Activitymentioning
confidence: 99%
“…In this complex, Axin and APC function as scaffold proteins, and facilitate the phosphorylation of β‐catenin at the N‐terminus by GSK3β . Recent study showed that GSK3β activation induced differentiation and decreased proliferation of human GBM cells, while small interfering RNA against GSK3β suppressed the induced GBM cell differentiation . Our data indicates that GSK3β, as a negative regulator of Wnt/β‐catenin signaling pathway, may be downstream of Sohlh1.…”
Section: Discussionmentioning
confidence: 64%